Use of Eculizumab in Atypical Hemolytic Uremic Syndrome, Complicating Systemic Lupus Erythematosus. Issue 6 (September 2016) - Bermea, Rene S.; Sharma, Niharika; Cohen, Kenneth; Liarski, Vladimir M.
Abstract : Abstract: Atypical hemolytic uremic syndrome is characterized by the presence of thrombocytopenia, microangiopathic hemolytic anemia, and end-organ injury. In this report, we describe two patients with systemic lupus erythematosus who presented with findings compatible with atypical hemolytic uremic syndrome, complicated by acute kidney injury that was refractory to conventional therapies. Both patients exhibited a response to eculizumab, a monoclonal antibody to complement protein C5, with stabilization of their platelet count. On 1-year follow-up from their initial presentation, their hematologic disease remained in remission without recurrence.